2008
DOI: 10.3329/bjar.v32i3.544
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and gene action in okra

Abstract: Forty two hybrids generated by crossing three testers with fourteen lines were studied along with parents for studying heterosis and gene action for days to first flowering, days to 50 percent flowering, fruit weight, fruit length, plant height, number of seeds per fruit, 100-seed weight and fruit yield per plant during rainy season and summer season of 2002-03

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…However, variance due to parent's verses hybrids was not significant for internodal length, stem girth, days to 50 per cent flowering, fruit diameter and number of ridges per fruit. Similar results were obtained by Mehta et al, 2007 andHosamani et al, 2008.…”
Section: Parents Vs Hybridssupporting
confidence: 90%
“…However, variance due to parent's verses hybrids was not significant for internodal length, stem girth, days to 50 per cent flowering, fruit diameter and number of ridges per fruit. Similar results were obtained by Mehta et al, 2007 andHosamani et al, 2008.…”
Section: Parents Vs Hybridssupporting
confidence: 90%
“…Heterosis breeding for yield and its components were extensively studied. Several workers have reported the occurrence of heterosis in fruit yield of okra and its attributing traits (Mehta et al, 2007;Jindal et al, 2009) [11,6] . The exploitation of heterosis is largely dependent on the screening and identification of diverse genotypes that could be produced by better combinations of important yield and yield contributing traits.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, heterosis for yield and its components were extensively studied. Several research workers have reported occurrence of heterosis in considerable quantities for fruit yield and its various components (Venkataramani, 1952;Joshi et al, 1958;Partap and Dhankar, 1980;Elangovan et al, 1981;Partap et al, 1981;Mehta et al, 2007;Weerasekara et al, 2007;Jindal et al, 2009). The ease in emasculation and very high percentage of fruit setting indicates the possibilities of exploitation of hybrid vigour in okra.…”
mentioning
confidence: 99%